Gender as a ‘Discursive Practice’ in Romance Discourse - Moussaoui, Abdelghani (International Journal of Language and Literary Studies, 2024)
This paper calls into question the cultural discourse behind writing and reading popular romances in the Western sphere. Within the framework of orientalist discourse, this paper examines the trope of gender construction in Rebecca Stratton’s The Silken Cage. It unveils Western female writers’ complicity, Stratton as a prototype, in the perpetuation of orientalist discourse through gendering the oriental ‘Other’. Stratton’s romance is worthy of scrutiny by virtue of displaying how gender colors the hegemonic discourse of representation. This paper is indebted to the postcolonial theory. After the analysis of the chosen account, it was inferred that Rebecca Stratton partakes in the replication of the orientalist ideas and images that have been already propagated by ‘white’ male writers about the gendered Moroccan ‘Other’. ‘Harem’ is presented in The Silken Cage as an arena where these gender misrepresentations about Morocco, as a subject and a culture, are articulated. Notably, Stratton’s mode of representation is marked by ‘ambivalence’; given its racist discourse, the novel sways between relegating and praising the ‘Other’. Stratton’s romance as a manifestation of a cultural potentiality deserves to be examined due to its location within the framework of distinctiveness between the ‘Self’ and the ‘Other’.